Determinants and economic consequences of colonization: A global analysis - Arhan Ertan; Louis Putterman; Martin Fiszbein (Brown University, Department of Economics, 2012)
Research on economic growth suggests that the era of colonization has had an impact on the levels of economic development of countries around the globe. However, why some countries were colonized early, some late, and others not at all, and what effect these differences have had on current income, has not been studied systematically. In the first part of this paper, we show that both the occurrence and the timing of colonization can be explained by (a) differences in levels of pre-1500 development, (b) proximity to the colonizing powers, (c) disease environment, and (d) latitude. In the second part, we analyze the developmental consequences of colonization while taking the endogeneity of colonization's occurrence and timing into account. Whereas naïve estimates can suggest large impacts, we find that neither the fact nor the timing of colonization affect income today once colonization's impact on the composition of the population and the quality of institutions is controlled for.
Keywords: O11; O13; O40; O57; 330; Colonization; Growth; Institutions; Pre-Modern Development; Migration